Platelet count and retinopathy of prematurity, a systematic review and meta-analysis - Zeng, Qian; Wang, Ling; Li, Yurong; Yue, Yuanyuan; Lv, Xin (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to investigate the relationship between platelet count (PLT) and retinopathy of prematurity (ROP), with the goal of identifying a straightforward screening method for the early detection of ROP.MethodsA systematic search was conducted in PubMed, EMBASE, Web of Science, Cochrane Library, and ClinicalTrials.gov from January 2005 to 26 September 2023. Subsequently, a subgroup analysis was performed.ResultsThis meta-analysis included ten studies involving 1762 neonates, with 747 cases of ROP identified. The pooled analysis indicated a significant decrease in mean platelet count among the ROP group compared to the non-ROP group (mean difference: −18.65, 95% confidence interval: −22.80 to −14.50, P < .00001). Subgroup analysis indicated that the heterogeneity in the results can be attributed to factors such as the location of the studies, gestational age (GA), and publication time.ConclusionDecreased PLT counts may be associated with the occurrence of ROP. The PLT count should be standardized according to the detection location, detection time and GA.